MEASURES TO REST-REDUCE AND PARDON PRISONERS IN THAILAND - Limprasert, Sanyapong (Rangsit Journal of Law and Society, 2021)
The imprisonment is decided by the court in a large number of cases, despite the growing attempts to enforce other compulsory measures, particularly fine and reprieve. The increase in the number of the prisoners affects the budget and the effectiveness of the correctional management, including the supervision and the development of the inmates’ behavior. The solutions of such issue from within the prisons such as the reduction of the number of the prisoners by the suspension-reduction and the pardon of the prisoners, and the improvement of the inmates’ behaviors to decrease the recidivism are the essential issue which shall be studied in this research. Therefore, the objectives of the research are to study and analyze 1). The implementation of the suspension-reduction and the pardon of the prisoners as the legal measures 2). The suspension-reduction and the pardon of the prisoners in foreign countries. For instance, the United Kingdom, the United States of America, Japan, and the Federal Republic of Germany. According to the research, the suspension-reduction and the pardon of the prisoners under the condition that the inmates must improve their behaviors, have persuaded the prisoners to behave, concentrate on the study and occupational training, and collect the merit. Consequently, the number of the inmates in the prison is reduced permanently through such rehabilitation. Furthermore, the individualization punishment must be implemented by planning and assess each inmate individually. There also should be the laws regarding the rehabilitation of prisoners in particular. Moreover, the private sector and the social societies should be more included in the enforcement process.